2020
DOI: 10.1111/ene.14466
|View full text |Cite
|
Sign up to set email alerts
|

Large vessel stroke in six patients following SARS‐CoV‐2 infection: a retrospective case study series of acute thrombotic complications on stable underlying atherosclerotic disease

Abstract: Background and purpose: Ischaemic stroke has been described in association with COVID-19. Several pathophysiological mechanisms have been suggested, i.e. prothrombotic state, cardiac injury etc. It was sought to assess the potential association between ischaemic stroke associated with SARS-CoV-2 infection and underlying atherosclerotic lesions. Methods: A retrospective analysis of stroke related to large vessel occlusion was conducted amongst patients with SARS-CoV-2 infection and underlying mild atherosclerot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 13 publications
3
11
0
2
Order By: Relevance
“…Similarly, the formation of atherosclerotic thrombus in the arteries has been reported in recent studies[ 177 ]. Lapergue et al [ 177 ] reported COVID-19 patients that showed the development of large thrombus in the cervical carotid artery with underlying mild non-stenosing atheroma.…”
Section: Role Of Atherosclerosis Imaging In Diabetes Patients During supporting
confidence: 69%
“…Similarly, the formation of atherosclerotic thrombus in the arteries has been reported in recent studies[ 177 ]. Lapergue et al [ 177 ] reported COVID-19 patients that showed the development of large thrombus in the cervical carotid artery with underlying mild non-stenosing atheroma.…”
Section: Role Of Atherosclerosis Imaging In Diabetes Patients During supporting
confidence: 69%
“…( Table I ). Another 2 COVID-19 patients with CCA totally occluded have been published, 22 , 23 these cases were excluded from the review because they did not meet our inclusion criteria. All patients presented with stroke as the chief symptom, and COVID-19 manifestations of mild severity.…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts to the NIHSS of 40 in the patient with basilar occlusion, which was reported in 12.5% of the overall included patient pool. Re-evaluation of the NIHSS at 24 h after presentation, which was reported in three of the eight studies, demonstrated no significant difference with the NIHSS at presentation, suggesting EVT has minimal effect in the acute phase [ 19 , 20 •].…”
Section: Discussionmentioning
confidence: 99%